Access to public school education for students with disabilities: United States and Ukraine - Weishaar, Phillip M.; Weishaar, Mary Konya (Social Welfare: Interdisciplinary Approach, 2011)
Although Ukraine and the United States developed their education systems under different contexts and histories, both struggled with providing access to public school education for students with disabilities. This article describes the different paths each country took leading to the development of access to a public school education for students with disabilities. Implications for Ukraine are detailed.